The Happiness Index as a New and Complementary Measurement of Development as Applied to Each Province of Indonesia - Hadi, Nafik Umurul; Ananda, Candra Fajri; Pudjiharjo, Pudjiharjo; Khusaini, Moh. (International Journal of Economics and Financial Issues, 2018)
Efforts of the governments of various states to raise the level of social welfare by means of developmental mechanisms, one of which is the Happiness Index (HI) as a new and complementary measurement of the outcomes of development, always experiences policy transformation. Based on the Multidimensional Scaling (MDS) method of analysis, at provincial level (of all 33 provinces of Indonesia) 4 grouping of HI, according to Economic and non-Economic elements. Based on the results of the study, each area needs to use the HI measurement as one of the indicators for quantifying the outcomes of development in the area. The findings also revealed the importance of considering social aspects as determinants of community happiness. Consequently the central and regional governments need to consider the inclusion of HI as one of the accompaniments to the economic indicators especially in the current era of decentralisation. Keywords: Development Indicators, Happiness Index, Economic and Non-economic. JEL Classifications: O24 I3